2011
DOI: 10.1108/18325911111164204
|View full text |Cite
|
Sign up to set email alerts
|

What determines ABC success in mature sites?

Suzanne Byrne

Abstract: PurposeThe purpose of this paper is to examine ABC success determinants in mature ABC sites. Methodology The study surveys 65 managers of service and manufacturing organizations using ABC. FindingsThe stepwise regression results indicate that top management support is the key determinant of ABC success in mature ABC sites. Research ImplicationsThis research shows that top management support continues to be critical to ongoing ABC success. Past research has shown that top management support is critical in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
2
12
0
6
Order By: Relevance
“…According to the research by Elhamma and Zhang (2013) in Morocco using a sample size of 48 industrial enterprises with 48% consisting of SME and 52% consisting of large firms, it was found that the influence of the external environment such as market competitiveness resulted to the implementation of ABC. Furthermore Byrne (2011) found that the level of the external environment was found to be a contributing factor in the implementation and success of the ABC system. As such, the following hypothesis is developed:…”
Section: Relationship Between the External Environment And The Implemmentioning
confidence: 99%
“…According to the research by Elhamma and Zhang (2013) in Morocco using a sample size of 48 industrial enterprises with 48% consisting of SME and 52% consisting of large firms, it was found that the influence of the external environment such as market competitiveness resulted to the implementation of ABC. Furthermore Byrne (2011) found that the level of the external environment was found to be a contributing factor in the implementation and success of the ABC system. As such, the following hypothesis is developed:…”
Section: Relationship Between the External Environment And The Implemmentioning
confidence: 99%
“…Research measuring the success of ABC prefer multidimensional measures. For example, Baird et al (2004) used Gosselin's (1997 and Byrne's (2011) success model to measure the success of ABC implementation. This was divided into user attitude, technical characteristics, perceived usefulness in improving user job performance, and organizational process.…”
Section: Measurement Of Abc Implementation Successmentioning
confidence: 99%
“…Mais recentemente, dada a dificuldade em se construir um conjunto de fatores sólidos sobre a adoção do ABC, foram testados os fatores apresentados por Shields (1995), e apenas três (apoio da alta gerência, adequação dos recursos e educação continuada) demonstraram similitude com o sucesso do ABC (Byrne, 2011). Novos fatores explicaram a divergência apresentada entre os estudos: (i) estágio de implantação e utilização do método e (ii) o segmento de atuação das empresas (Shields, 1995;Byrne, 2011).…”
Section: Problematizaçãounclassified
“…Novos fatores explicaram a divergência apresentada entre os estudos: (i) estágio de implantação e utilização do método e (ii) o segmento de atuação das empresas (Shields, 1995;Byrne, 2011). Na saga por entender o comportamento da adoção do ABC, um relevante universo de empresas geralmente é desprezado das amostras, qual seja, o das empresas que rejeitaram a utilização do método ou das que o implantaram e abandonaram a utilização após determinado período.…”
Section: Problematizaçãounclassified
See 1 more Smart Citation